Understanding health literacy and digital healthy diet literacy in rural women in Türkiye: a cross-sectional study on social media use and Mediterranean diet adherence - Batu, Zehra; Kalaman, Sefer; Batu, Mikail; Şentürk, Zülfiye Acar; İplikçi, Handan Güler; Vural, Nazmi Ekin; Taşkıran, İlkay Burak (Frontiers in Public Health, 2025)
BackgroundHealth literacy (HL) is the ability to search for, acquire, understand, interpret, and act upon basic information, concepts, and services about health to make correct and informed health decisions about. In terms of public health, low HL can lead to negative health outcomes, increased healthcare costs, increased medical and medication errors, disruption of the treatment process, and increased mortality.MethodsThis study investigated factors associated with HL and digital healthy diet literacy (DDL), focusing on rural women using social media. This cross-sectional study included women aged 18–65 years living in rural areas in Türkiye between 01/12/2023 and 29/02/2024. The variables examined regarding HL and DDL are duration and purpose of use of the internet and social media, compliance with the Mediterranean diet, and sociodemographic characteristics. HL and DDL were evaluated using the Turkish version of HLS-SF12 and DDL scale.ResultsThe maximum score that can be obtained from the HLS-SF12 and DDL scale is 50 and the average index values of the participants were determined as 26.70 and 21.99, respectively. HL and DDL index scores were affected by the purpose and duration of internet/social media use. HL and DDL index scores were found to be higher in those who had a diet history under dietitian counseling, university graduates, those who adhered to the Mediterranean diet, and those with higher household income. In addition, it was determined that DDL index and HL index correlated with Mediterranean Diet Adherence Screener (MEDAS) score and Body Mass Index (BMI).ConclusionHL index and DDL index scores differ depending on the duration and purpose of internet use, age, presence of chronic disease, education level, and income level. It is recommended to conduct further studies evaluating the use of social media as a tool to promote HL, DDL, and healthy eating behaviors in different populations.